Unmet Needs for the Treatment of Chronic Hepatitis E Virus Infection in Immunocompromised Patients - Nassim Kamar; Arnaud Del Bello; Florence Abravanel; Qiuwei Pan; Jacques Izopet (Viruses, 2022)
Hepatitis E virus (HEV) is the most prevalent hepatitis virus worldwide. Genotypes 3 (HEV3) and 4 (HEV4) as well as rat HEV can lead to chronic hepatitis E and cirrhosis in immunosuppressed patients. Within the last decade, several options for treating chronic hepatitis have been developed and have achieved a sustained virological response. However, there are still unmet needs such as optimizing immunosuppression to allow HEV clearance with or without ribavirin, as well as alternative therapies to ribavirin that are discussed in this paper.